MECHANISMS FOR IMPROVING THE FORMATION AND ASSESSMENT OF COMPETITIVE COMPETENCIES IN THE SELECTION OF CIVIL SERVICE CANDIDATES THROUGH OUTSOURCING - Isroilov, Islomiddin (International Conference on Business & Management, 2026)
this study examines the theoretical and practical aspects of applying outsourcing mechanisms to improve the selection process of candidates for the civil service. The research substantiates the necessity of developing a system for identifying and assessing competitive competencies through the use of modern HR technologies, psychometric assessment methods, and cooperation with private assessment centers. This approach enhances transparency in personnel selection, strengthens meritocratic principles, and increases the overall effectiveness of the recruitment process. As a result of the study, recommendations are proposed for developing an optimized outsourcing-based model for candidate selection and a set of evaluation indicators for assessing civil service applicants.